A financial analysis of the potential of dead trees from the boreal forest of eastern Canada to serve as feedstock for wood pellet export. (15th July 2017) - Barrette, Julie; Thiffault, Evelyne; Achim, Alexis; Junginger, Martin; Pothier, David; De Grandpré, Louis
Highlights: The spruce budworm outbreak will increase the amount of dead trees in Eastern Canada. Wood degradation did not affect the eligibility of dead trees for pellet production. Lumber and pulp production remains the most profitable option except in small trees. A drop by 20–40% in wood chip price would make pellet and pulp scenarios equivalent. Abstract: Global demand for forest biomass feedstock has increased drastically in recent years, mainly due to the implementation of policies and strategies for climate change mitigation and renewable energy production in many jurisdictions. The biomass from dead trees has been recognized by the International Panel on Climate Change (IPCC) as a promising source of forest biomass for bioenergy at the global scale both because of its wide scale availability and its potential to limit global warming. In eastern Canada, dead trees are not only very abundant but are also widely perceived by lumber and pulp and paper producers as contaminants in the wood supply chain with marginal profitability. The general aim of this study was to determine the conditions of profitability of an eastern Canada independent sawmill ( i.e., unaffiliated with a pulp plant) to produce pellets destined for international export using either co-products or roundwood from dead trees as feedstock. We compared the yield and monetary value of dead trees at various sizes and degradation levels for the production of wood pellets, alone or in conjunction with the production of lumber, to current market conditions. Our results suggest that using dead trees for lumber and pellets is almost as profitable as using them for lumber and pulp, with a difference of about 1–12% depending on tree size. Dead trees from all classes of wood degradation could serve as an interesting feedstock for pellets because wood density was only slightly affected by wood degradation. Small dead trees (DBH < 15 cm) could serve for all scenarios, as the difference between revenues and costs remained generally minimal between them. Larger dead trees did not appear to represent a financially viable option under current market prices, unless suitable subsidies or other types of financial support are provided. The sustainability criteria applied by European consumers could therefore be a determining factor for the future importance of dead trees from eastern Canada as a source of feedstock for wood pellet production.